2022
DOI: 10.1093/jb/mvac073
|View full text |Cite
|
Sign up to set email alerts
|

The role of TREM2 N-glycans in trafficking to the cell surface and signal transduction of TREM2

Abstract: Variants of triggering receptor expressed on myeloid cells 2 (TREM2) are associated with an increased incidence of Alzheimer’s disease, as well as other neurodegenerative disorders. TREM2 is glycosylated in vitro and in vivo, but the significance of the modification is unknown. We previously established a sensitive and specific reporter cell model involving cultured Jurkat cells stably expressing a luciferase reporter gene and a gene encoding a TREM2DAP12 fusion protein to monitor TREM2-dependent signalling. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Taken together, the thermal denaturation study identified a critical role of N79 glycosylation on the thermal stability of TREM2. Interestingly, these two N glycans were shown to facilitate trafficking to the cell surface and signal transduction of full-length, membrane-tethered TREM2 in cultured cells, 39 but the functional implications of glycosylation at N20 and N79 for the soluble TREM2 ectodomain remain to be determined.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Taken together, the thermal denaturation study identified a critical role of N79 glycosylation on the thermal stability of TREM2. Interestingly, these two N glycans were shown to facilitate trafficking to the cell surface and signal transduction of full-length, membrane-tethered TREM2 in cultured cells, 39 but the functional implications of glycosylation at N20 and N79 for the soluble TREM2 ectodomain remain to be determined.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Taken together, the thermal denaturation study identified a critical role of N79 glycosylation on the thermal stability of TREM2. Interestingly, these two N glycans were shown to facilitate trafficking to the cell surface and signal transduction of full-length, membrane-tethered TREM2 in cultured cells, 39 but the functional implications of glycosylation at N20 and N79 for soluble TREM2 ectodomain remains to be determined.…”
Section: Refolded Synthetic Trem2(19-134) Enhanced Microglial Phagocy...mentioning
confidence: 99%
“…24 N-linked glycosylation of Trem2-FL affects its stability, trafficking to the PM, and post-activation signal transduction. 25 However, the effects of sialylation on Trem2 remain elusive.…”
Section: Introductionmentioning
confidence: 99%